RELATIONSHIP BETWEEN MUNICIPAL GOVERNMENT REVENUE COLLECTION AND SERVICE DELIVERY IN RUKUNGIRI MUNICIPALITY. A CASE STUDY DESCRIPTIVE, CROSS-SECTIONAL RESEARCH DESIGN. - Nalubanga, Carol; Bakashaba, Edmand; Sendagi, Muhammad (Student's Journal of Health Research Africa, 2023)
Background. Aim: To determine the relationship between municipal government revenue collection and service delivery in Rukungiri Municipality. Methodology A case study, descriptive, cross-sectional research design was used for this study. The study adopted both qualitative and quantitative approaches. A case study design was adopted because it enabled the researcher to carry out an in-depth investigation into the concepts under study. The entire population of Rukungiri Municipality is targeted in this research. Also, the municipality has 51 civil servants/technical staff, 20 political leaders (councilors) at municipal and Division levels, 20 taxpayers, 7 service providers, and 25 community projects’ beneficiaries. This is based on different stakeholders’ information relevance in their respective positions. Therefore, the population of the study was 1400 people. A sample of 302 respondents were selected Results One of the findings mentioned is the importance of local revenue in decentralized societies. While it’s true that local revenue plays a significant role in financing local government operations and service delivery, it is important to consider the capacity of local governments to effectively collect taxes. Many local governments in developing countries face challenges in revenue collection, including limited tax bases, weak tax administration capacity, and high levels of tax evasion and informality. Therefore, simply relying on local revenue may not be sufficient to meet the financing needs of local governments and ensure adequate service delivery. Conclusion The findings indicate that there was a positive and moderately strong relationship between revenue collection and service delivery (r = 0.719). This relationship implies that the municipality is using its collected revenue to fund its expenditures for service delivery. Recommendation Strengthen local revenue collection: Rukungiri Municipality should enhance its capacity to collect local taxes and fees efficiently. This can involve investing in modernizing revenue collection systems, training staff, and conducting public awareness campaigns to ensure compliance.